The basics of public budgeting and financial management : a handbook for academics and practitioners - Menifield, Charles (Hamilton Books, 2021)
The Basics of Public Budgeting and Financial Management brings budgetary theory and practice together, filling the void between the two that has existed in the field of budgeting and public finance. This book bridges the gap by providing students with applications and exercises that reinforce budgetary theory. These exercises are the key to ensuring that students leave the classroom with knowledge and marketable skills. Specifically, students will be exposed to basic budget and finance concepts, but more importantly they will complete assignments where they apply the information in various settings. For example: creating tax structures, conducting a financial management plan, risk assessments, cost benefit analysis, and so on. This handbook also shows students how to best utilize tools that allow them to visually display budgets and other budgetary data. Students will gain the solid foundation needed to begin work in a budget office. While the original purpose of the book is the same, the third edition of the book provides a few new thematic sections as well as homework questions and classroom assignments that reinforce the topical areas. The ancillary materials make the process very easy for an instructor to organize their lectures around thematic areas. The book is a must read for instructor's who are considering a course that introduces students to budgeting and finance and those who want student's to learn the basic components of budgeting and financial management.- Resumé vydavatel
Keywords: veřejné finance; veřejné rozpočty; státní rozpočet; rozpočtová politika; finanční management; finanční plánování; public finance; public budgeting; budget; budgetary policy; financial management; financial planning; elektronické knihy; příručky; electronic books; handbooks and manuals